Sale of medicinal herbs in pharmacies and herbal stores in Hurlingham district, Buenos Aires, Argentina - Bach, Hernán Gerónimo (2014)
In this paper, the sale of medicinal plants was described in the urban city of Buenos Aires, Argentina. Semi-structured interviews were conducted with pharmacists and herb store owners about different characteristics of retail. Likewise, different types of retailers were compared, and the phytomedicine degree of acceptance was consulted. The percentage of customers who buy medicinal plants in herb stores is higher than in pharmacies. The five most demanded species were: "malva" (Malva sp.), 18%; "manzanilla" (Matricaria recutita), 13%; "tilo" (Tilia sp.), 12%; "cuasia" (Picrasma crenata), 8%; and "boldo" (Peumus boldus), 7%. In like manner, the most demanded mixes of species were those that had slimming properties, 21%; digestive, 17%; sedative and diuretic, 13%. Of the 32 most frequently requested species, only 13 are native. Phytomedicines were widely accepted in the different kinds of retail stores. It was also emphasized that, contrary to the usual assumption, the choice to consume plants is cultural rather than economic. Due to the acceptance observed in the use of phytomedicines, it must be emphasized the potential that Argentina possesses for the development of this industry.